THE STUDENT PRONUNCIATION SKILLS IN ENGLISH VOWELS SOUND - Didik Santoso; Nasywa Faira Syifa Indra; Sabrina Salsabila; Tiara Adelia; Maulana Budi Satria Siregar (LANGUAGE : Jurnal Inovasi Pendidikan Bahasa dan Sastra, 2026)
ABSTRACT This study aimed to examine EFL students' English vowel pronunciation skills and identify the factors influencing their pronunciation performance. Although pronunciation is a fundamental component of communicative competence, studies investigating the factors affecting English vowel pronunciation among EFL learners in Indonesian higher education remain limited. This research employed a quantitative correlational design involving 40 students from the English Education Study Program at the State Islamic University of North Sumatra. Data were collected through a pronunciation test to assess students' ability to produce English vowel sounds and a questionnaire measuring first language interference, English exposure, teaching methods, and learning motivation. The data were analyzed using descriptive statistics, correlation analysis, and regression analysis. The findings revealed that the students' pronunciation ability was classified as [insert category]. English exposure and learning motivation showed significant positive correlations with pronunciation skills, whereas first language interference was negatively associated with pronunciation accuracy. Regression analysis further indicated that these variables significantly predicted students' pronunciation performance (R² = [insert]; p < .05). In conclusion, increased English exposure and stronger learning motivation contribute positively to the improvement of English vowel pronunciation, while first language interference remains a major barrier to pronunciation accuracy. These findings highlight the importance of implementing instructional strategies that increase learners' exposure to English while reducing the influence of the first language in EFL pronunciation instruction. ABSTRAK Penelitian ini bertujuan menganalisis keterampilan pelafalan bunyi vokal bahasa Inggris serta faktor-faktor yang memengaruhinya pada mahasiswa EFL. Meskipun pelafalan berperan penting dalam keterpahaman komunikasi, kajian mengenai faktor-faktor yang memengaruhi pelafalan bunyi vokal pada pembelajar EFL di perguruan tinggi Indonesia masih terbatas. Penelitian ini menggunakan desain kuantitatif korelasional yang melibatkan 40 mahasiswa Program Studi Pendidikan Bahasa Inggris Universitas Islam Negeri Sumatera Utara. Data dikumpulkan melalui tes pelafalan dan kuesioner yang mengukur interferensi bahasa pertama, paparan bahasa Inggris, metode pengajaran, dan motivasi belajar. Analisis data dilakukan menggunakan statistik deskriptif, uji korelasi, dan regresi. Hasil penelitian menunjukkan bahwa kemampuan pelafalan mahasiswa berada pada kategori [isi kategori]. Paparan bahasa Inggris dan motivasi belajar berkorelasi positif secara signifikan dengan keterampilan pelafalan, sedangkan interferensi bahasa pertama berkorelasi negatif. Analisis regresi menunjukkan bahwa faktor-faktor tersebut berpengaruh signifikan terhadap keterampilan pelafalan mahasiswa (R² = [isi]; p < 0,05). Disimpulkan bahwa peningkatan paparan bahasa Inggris dan motivasi belajar, disertai upaya mengurangi interferensi bahasa pertama, berkontribusi terhadap peningkatan akurasi pelafalan bunyi vokal pada pembelajar EFL.